Different acute effects of fructose and glucose administration on hepatic fat content - Dusilová, Tereza; Kovář, Jan; Drobný, Miloslav; Šedivý, Petr; Dezortová, Monika; Poledne, Rudolf; Zemánková, Kateřina; Hájek, Milan (The American journal of clinical nutrition, 2019)
BACKGROUND: Diets rich in fat and added sugars (especially fructose) play an important role in the pathogenesis of nonalcoholic liver disease (NAFLD), but there is only limited information on the acute effects of these nutrients on hepatic fat content (HFC). OBJECTIVES: We therefore explored how the administration of high-fat load, glucose, fructose, and combinations thereof affects HFC measured in vivo using proton magnetic resonance spectroscopy (1H-MRS) in healthy subjects. METHODS: Ten healthy nonsteatotic male volunteers (age 38.5 ± 9.6 y, body mass index [BMI, kg/m2] 26.9 ± 2.7) underwent, in random order, 6 experiments, each lasting 8 h, that included: 1) fasting; 2) a high-fat load (150 g of fat [dairy cream] at time 0); 3) glucose (3 doses of 50 g at 0, 2, and 4 h); 4) a high-fat load with glucose; 5) fructose (3 doses of 50 g at 0, 2, and 4 h); and 6) a high-fat load with fructose. HFC was measured using 1H-MRS prior to test meal administration (before time 0) and at 3 and 6 h. Plasma concentrations of triglycerides, nonesterified fatty acids, glucose, and insulin were monitored throughout each experiment. RESULTS: HFC increased to 119 ± 19% (P < 0.05) and 117 ± 17% (P < 0.01) of baseline when subjects consumed a high-fat load alone or a high-fat load with fructose, respectively, but was not affected when glucose was coadministered with a high-fat load. HFC was not affected when subjects had fasted or had consumed repeated doses of fructose. When subjects were administered 3 doses of glucose, HFC dropped to 85 ± 13% (P < 0.05) of baseline. CONCLUSIONS: Our results demonstrate that fructose and glucose have a different immediate impact on HFC in humans in vivo. Clinical trial registry: The study was registered at clinicaltrials.gov and obtained clinicaltrials.gov identifier: NCT03680248.
Keywords: tuky; játra; fructose; Triglycerides; healthy volunteers; kyseliny mastné neesterifikované; Humans; glucose; mladý dospělý; dospělí; proton magnetic resonance spectroscopy; lidé; fruktosa; glukosa; mladiství; hepatic fat content; Adult; triglyceridy; Liver; Male; Insulin; Glucose; Adolescent; Fatty Acids, Nonesterified; Fats; Young Adult; dietary fat; nonesterified fatty acids; mužské pohlaví; Fructose; insulin; inzulin